Feasibility and safety of planned early discharge following laparotomy in gynecologic oncology with enhanced recovery protocol including opioid-sparing anesthesia - Kuznicki, Michelle L.; Yasukawa, Maya; Mallen, Adrianne R.; Lam, Clarissa; Eggers, Erica; Regis, Jefferson; Wells, Ali; Todd, Sarah L.; Robertson, Sharon E.; Tanner, Jean-Paul; Anderson, Matthew L.; Rutherford, Thomas J. (Frontiers in Surgery, 2023)
Objective: To evaluate feasibility and safety of planned post-operative day 1 discharge (PPOD1) among patients who undergo laparotomy (XL) within the department of gynecology oncology utilizing a modified enhanced recovery after surgery (ERAS) protocol including opioid sparing anesthesia (OSA) and defined discharge criteria.In this prospective, observational cohort study, patients undergoing XL and minimally invasive gynecologic surgery (MIS) were enrolled after the departmental implementation of a modified ERAS protocol. Primary outcome was quality of life (QoL) using SF36, PROMIS GI, ICIQ-FLUTS at baseline, 2-and 6-week postoperative visits. Statistical significance was assessed using two-tailed Student's t-tests and non-parametric Mann-Whitney two-sample tests.Results: Of 141 subjects, no significant demographic differences were observed between XL group and MIS group. The majority of cases, 84.7 % (61), in XL group were for gynecologic malignancy (vs MIS group; 21 (29.2%), p<0.001). All patients tolerated OSA. XL group required a higher intraoperative opioids (7.1±9.2 Morphine Miligram Equivalents (MME) vs 3.9±6.9 MME, p=0.02) and longer surgical time (114.2 ± 41 mins vs 96.8 ± 32.1 mins, p =0.006). No significant difference was noted in the opioid requirements at immediate postoperative phase, the rest of postoperative day (POD) 0 or POD 1. In XL group, 69 patients (73.6%) were successfully discharged home on POD1. There was no increase in the PROMIS score at 2 weeks, 6 weeks compared to preoperative phase. Readmission rates within 30 days after surgery (XL 4.2% vs MIS 1.4 %, p=0.62), rates of surgical site infection (XL 0% vs MIS 2.8%, p=0.24), and the mean number of post discharge phone calls (0 vs 0, p=0.41) were comparable between two groups. Although QoL scores were significantly lower than baseline in four of the nine QoL domains at 2 weeks post-laparotomy, all except physical health recovered by the 6-week timepoint.Conclusions: PPOD1 is safe and feasible strategy for XL performed in the gynecologic oncology department. PPOD1 did not increase opioid requirements, readmission rates compared to MIS and patient reported constipation, nausea/vomiting compared to preoperative phase.